Hard times - Dickens, Charles, 1812-1870.; Davies, David Stuart; Collector's Library (London : Collector's Library, 2008)
Mr. Thomas Gradgrind, school headmaster in Cokestown, a northern English village beset by industrialism, runs his family and his school with a rigid adherence to facts, but his daughter's loveless marriage, his son's involvement with gambling and robbery, and his encounters with a variety of characters force him to recognize the value of the human heart.
Young Adult
Keywords: Social problems -- Fiction; England -- Fiction